A survey of East Palaearctic Gnaphosidae (Araneae). 4. A review of Fedotovia Charitonov, 1946 - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2015)
Fedotovia Charitonov, 1946 is a genus of Gnaphosinae earlier known to contain only two species: F. uzbekistanica Charitonov 1946 (♂♀, type species) and F. mongolica Marusik, 1993 (♀). Revision of available material reveals two more species, both from Mongolia: F. mikhailovi sp. n. (♂♀) and F. feti sp. n. (♂♀). All four species have very similar copulatory organs and can be more easily differentiated by somatic characters (body size, spination, eye formula). All species are described and illustrated.